Primary Solitary Fibrous Tumor of the Thyroid - Report of a Case and Review of the Literature - Song, Zhigang (Ivyspring International Publisher, 2011)
Solitary fibrous tumor (SFT) is a rare spindle-cell neoplasm, especially in the thyroid. We report a case of primary solitary fibrous tumor of the thyroid gland in a 37 year-old Chinese man. The tumor was characterized by bland-looking spindle cells admixed with thin and thick collagen fibers. On immunohistochemistry study indicated that tumor cells were diffusely positive for CD34, Bcl-2 and CD99, and negative for Desmin, NSE, SMA, S-100, and CD68. The patient remains well 16 months after excision. The morphologic and immunohistochemical features of the thyroid SFTs are similar to their reported counterparts in other anatomic sites.